Eco soy de tus palabras: Tradiciones populares, tradiciones letradas e intercambios simbólicos en la poesía ibérica - Disalvo, Santiago (Colectivo Crítico, 2022)
This book is the result of a collective study, research, discussion and review project that began in 2014 at the IdIHCS, in the Faculty of Humanities and Educational Sciences of the National University of La Plata. From the paths traced by Curtius, Auerbach, Jauss and Ong, the fourteen studies that are part of this volume emerged and were written with the intention of generating a contribution for the dialogue of a cultural, transnational and diachronic reading of literature. Autores: Disalvo, Santiago (comp.); Calabrese, Martín Ezequiel (comp.); Lima, Damián; Rio Riande, Gimena del; Pavón, María Cecilia; Calvo, Florencia; Festini, Patricia; González, Ximena; Varela, Fernanda Soledad; Nusch, Carlos Javier; Stecher, Cecilia; De Oro, Camila; Chicote, Gloria; Natoli, Cecilia; Arata, Facundo.